Research on Production Efficiency and Ownership Concentration---Taking Steel Industry and Logistics Industry as Examples - et. al., Han-Hsing Yu , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The iron and steel industry is a basic industry in my country's industry and holds an important position in the national economy. My country's steel industry has serious overcapacity. As the country virtually promotes the supply-side structural reform of steel production capacity and the merger and reorganization of the industry, the steel market has begun to pick up, and corporate profits have radically improved. Use effectiveness analysis, project analysis and sensitivity after analysis of the financial performance evaluation of companies in the listed steel industry (30) and logistics companies (several), it is found that China's steel industry needs to focus on growth capacity and proficiency, and there are redundant operating capacity inputs and ineffective growth capacity output. According to the analysis results, fou